Gated audiovisual speech identification in silence vs. noise: effects on time and accuracy - Moradi, Shahram; Lidestam, Björn; Rönnberg, Jerker (Frontiers in Psychology, 2013)
This study investigated the degree to which audiovisual presentation (compared to auditory-only presentation) affected isolation point (IPs, the amount of time required for the correct identification of speech stimuli using a gating paradigm) in silence and noise conditions. The study expanded on the findings of Moradi et al. (under revision), using the same stimuli, but presented in an audiovisual instead of an auditory-only manner. The results showed that noise impeded the identification of consonants and words (i.e., delayed IPs and lowered accuracy), but not the identification of final words in sentences. In comparison with the previous study by Moradi et al., it can be concluded that the provision of visual cues expedited IPs and increased the accuracy of speech stimuli identification in both silence and noise. The implication of the results is discussed in terms of models for speech understanding.